Saberes docentes do ensino superior : desvelando saberes - Masini, Elís Regina (2009)
The human being, during life, faces difficulties to adapt himself to conditions in a society which is in development. It means he has the necessity to prepare himself for temporary certainties of the world, over unlimited knowledge and unpredictable situations. In this context, and based on the assumption that the main objective of education is to capacitate the man with cultural elements, the teacher and the university's function tacitly contributes to building a better society. Thus, the teacher is a key element in this context, and needs an extensive training. However, studies have shown that the university teacher learns to be like that by a process of socialization by the intuition or following other teachers' routine. Accordingly, this study aimed to understand the process and the production of knowledge of a group of teachers who work in higher education in the Course of Biological Sciences - Graduate Qualification. The focus of the discussion was the link between the knowledge acquired in training and the practice of teaching. Guided by testimonials, rescued by questionnaires and semi structured interviews with teachers, followed by a methodology guided by qualitative research with the focus on the analysis of discourse, in Foucault optics. In the data analyzed, it may be observed that the teacher in higher education, in particular in the Course of Biological Sciences - Graduate Qualification, in the absence of a specific teacher training, acquires experience and knowledge to solve everyday conflict situations in the teaching and learning process, promoting a new way of acting determining its own conduct of concepts reorganized in a different practice thus producing new professional knowledge.